EVALUASI TERHADAP PENYALURAN, PENGELOLAAN DAN PERTANGGUNGJAWABAN PENGGUNAAN DANA DESA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA PADA PEMERINTAH DAERAH KABUPATEN BINTAN (STUDI KASUS PADA DESA BERAKIT KECAMATANTEL - Salihi pro (EKONOMIKA, 2020)
This study aims to compare the mechanism of distribution, management and accountability of the use of village funds in the Government of Bintan Regency with the rules and regulations applicable. The method used in this research is descriptive qualitative method by conducting data collection through observation, literature study and interview with the authorized party. Village Funds are funds disbursed by the Central Government to help accelerate development in the villages, help improve the economy in the villages and also help the operational costs of village administration in order to maximize the maximum service for the villagers. Regulation of the Minister of Finance No. 93 / PMK.07 / 2015 has clearly set out procedures for the allocation, distribution, use, monitoring and evaluation of village funds. Therefore, village government officials are required to fully understand the prevailing regulations in order to manage, use and account for village funds maximally, correctly and accountable. Expenditure accountability is absolute in the use of village funds as a form of administrative and morally accountable. For that every State apparatus using State budget must be accountable properly and accountable.